A framework to integrate design for reliability and maintainability in modular product design. (9th April 2007) - Nepal, Bimal; Monplaisir, Leslie; Singh, Nanua
This paper presents a framework to optimise reliability and maintainability (R&M) of a product through modular design. A structured process is developed for incorporating three types of R&M metrics into the modular design. These metrics are failure potential and simplicity of module architecture, maintainability and maintenance commonality between the components, and serviceability of the module. In addition to reliability and maintainability, cost of modularisation is also taken into account for modules selection purpose. The metrics of modularisation costs are cost of interface to join the components, assembly resources requirements, and cost of reusability of modules. We use fuzzy logic and the goal programming models for developing the modular design. An example is presented to demonstrate the application of the proposed methodology.